Prioritetni zadaci prometne politike u službi strategije obnove i razvoja prometnog sustava Republike Hrvatske - Radačić, Željko (Promet - Traffic&Transportation, 2012)
Traffic policy as an integral part of the overall economic and development policy of any country refers to an interactive relation of objectives, measures, instatements and entities making its consistent segments requiring an optimum structure of the traffic system and its successful functioning. Defining the strategy of reconstruction and development of the Croatian traffic system refers to a higher degree of concretization, starting from the traffic-aspected assessment up to determining and defining the traffic policy. New political/legal and international conditions as the factors of the general environment in which Croatia shall act as an independent and sovereign counlly, the forthcoming period of reconstruction and economic development, the need for massive investments into the overall traffic system, particularly into the traffic infrastructure, all this calls for defining the strategy and strategic development trends of the entire traffic system and individual traffic aspects. The traffic policy should define priorities and strategic objectives while the system of corresponding legislative/legal and economic instruments should grant their materialization.